Studi Literatur: Analisis Hambatan, Faktor Pendorong, Dan Dampak Adopsi Sistem Informasi Akuntansi Digital Pada UMKM - Gracia Apriana Malau; Theresa Margareth Panjaitan; Natasha Romauli Setya; Rohni Bona Arta Saragih; Esa Setiana (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This article aims to analyze the barriers, drivers, and impacts of Digital Accounting Information Systems (AIS) adoption on Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The study uses a descriptive qualitative approach based on literature studies from various national and international journal sources, as well as official reports from government and related institutions. The study results indicate that the main barriers to Digital AIS adoption include financial constraints, low human resource competency, organizational cultural resistance, and concerns about data security. On the other hand, driving factors supporting adoption include increasingly user-friendly and cloud-based technology, government support through digitalization programs, market competitive pressures, and support from technology providers. The adoption of Digital AIS has positive impacts for MSMEs, such as increased operational efficiency, accountability and transparency of financial reports, easier access to financing, and increased data-based competitiveness. These findings emphasize the importance of collaboration between the government, technology providers, and MSMEs to accelerate the digitalization of the MSME sector in a sustainable manner.